AN ANALYSIS OF THE INSTRUMENTAL AND INTEGRATIVE MOTIVATION OF THE FIRST YEAR STUDENTS OF ENGLISH STUDY PROGRAM FKIP UNIVERSITAS RIAU IN THE LEARNING OF ENGLISH - Ria Luli Muktianingsih; Fadly Azhar; Eliwarti Eliwarti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Motivation is an essential factor that affects the process of foreign language acquisition. The objective of this research is to find out the level of motivation in learning English and the dominant type of motivation whether instrumental or integrative motivation. This research used descriptive quantitative method. The population of this research was the first year students of English Study Program FKIP Universitas Riau in academic year 2019/2020. The number of sample was taken based on Slovin formula; in which there were 55 students selected by simple random sampling technique. Questionnaires and interview were used to collect the data. The results from this study showed that the level of integrative motivation has mean score of 4.27 and instrumental motivation has mean score of 3.63. This result indicated that the dominant type of motivation of the first year students was integrative motivation rather than instrumental motivation.Key Words: Instrumental motivation, integrative motivation, learning English